Do ticks and Borrelia burgdorferi s.l. constitute a burden to birds? - Norte, A. (2013)
Ticks consume resources from their hosts shaping their life-history traits and are vectors of many zoonotic pathogens. Several studies have focused on the health effects of blood sucking ectoparasites on avian hosts, but there is limited information on the effects of ticks on adult and sub-adult birds, which may actively avoid ticks and are likely to present low infestation intensities. We evaluated the effects of the presence of feeding ticks and intensity of infestation on health variables of avian hosts. We also evaluated whether these variables were affected by tick infection by Borrelia burgdorferi sensu lato (s.l.) and by the presence of Borrelia infection on the birds’ skin. Presence of parasite association among ticks, haemosporidea and Borrelia within the bird-host was also tested. We found that infestation by ticks significantly increased heterophyl/lymphocyte ratio in Turdus merula suggesting increased stress. This was especially evident at high infestation intensities when a significant decrease in body mass and body condition (body mass corrected for size) was also observed. Erithacus rubecula infested with more than ten larvae tended to have lower haematocrit and blood haemoglobin. Plasma globulin concentration in T.merula tended to be affected by the presence of attached ticks and their infection with Borrelia, but this depended on the age of the bird. No association was detected among ticks, haemosporidea and Borrelia infection. We showed that ticks have detrimental effects on their avian hosts even under natural infestation conditions and that confirmed Borrelia reservoir hosts may also present symptoms of infection, though these may be subtle.